Clinical assessors’ working conceptualisations of undergraduate consultation skills: a framework analysis of how assessors make expert judgements in practice - Hyde, Catherine (Adv Health Sci Educ Theory Pract, 2020)
Undergraduate clinical assessors make expert, multifaceted judgements of consultation skills in concert with medical school OSCE grading rubrics. Assessors are not cognitive machines: their judgements are made in the light of prior experience and social interactions with students. It is important to understand assessors’ working conceptualisations of consultation skills and whether they could be used to develop assessment tools for undergraduate assessment. To identify any working conceptualisations that assessors use while assessing undergraduate medical students’ consultation skills and develop assessment tools based on assessors’ working conceptualisations and natural language for undergraduate consultation skills. In semi-structured interviews, 12 experienced assessors from a UK medical school populated a blank assessment scale with personally meaningful descriptors while describing how they made judgements of students’ consultation skills (at exit standard). A two-step iterative thematic framework analysis was performed drawing on constructionism and interactionism. Five domains were found within working conceptualisations of consultation skills: Application of knowledge; Manner with patients; Getting it done; Safety; and Overall impression. Three mechanisms of judgement about student behaviour were identified: observations, inferences and feelings. Assessment tools drawing on participants’ conceptualisations and natural language were generated, including ‘grade descriptors’ for common conceptualisations in each domain by mechanism of judgement and matched to grading rubrics of Fail, Borderline, Pass, Very good. Utilising working conceptualisations to develop assessment tools is feasible and potentially useful. Work is needed to test impact on assessment quality.